Examining the impact of acetylene on N-fixation and the active sediment microbial community - Fulweiler, Robinson W.; Heiss, Elise M.; Rogener, Mary Kate; Newell, Silvia E.; LeCleir, Gary R.; Kortebein, Sarah M.; Wilhelm, Steven W. (Frontiers in Microbiology, 2015)
Here we examined the impact of a commonly employed method used to measure nitrogen fixation, the acetylene reduction assay (ARA), on a marine sediment community. Historically, the ARA technique has been broadly employed for its ease of use, in spite of numerous known artifacts. To gauge the severity of these effects in a natural environment, we employed high-throughput sequencing to detect differences in acetylene-treated sediments versus non-treated control sediments after a seven hour incubation. Within this short time period, significant differences were seen broadly across all types of microbes identified in the sediment, implying that the changes induced by acetylene occur quickly. The results have important implications for our understanding of marine nitrogen budgets. Moreover, because the ARA technique has been widely used in terrestrial and freshwater habitats, these results may be applicable to other ecosystems.